Managerial overconfidence and the buyback anomaly - Andreou, Panayiotis; Cooper, Ilan; De Olalla Lopez, Ignacio Garcia; Louca, Christodoulos (My University, 2018)
While positive, long-run abnormal returns following share repurchase announcements are substantially lower when CEOs are overconfident. This effect is particularly strong for (i) difficult to value firms, such as small, young, non-dividend paying, distressed, and having negative earnings firms, (ii) firms with poor past stock return performance and high book-to-market ratio, indicators of possible overreaction to bad news, and (iii) financially constrained firms. Overall, these results are consistent with the mispricing hypothesis as a motive for repurchases and as an explanation for the buyback anomaly. Additionally, irrespective of the CEO’s level of confidence, abnormal returns are considerably larger for financially constrained firms, implying their managers require larger undervaluation due to the higher cost of capital.
Keywords: Share repurchase; Buybacks; Overconfidence; Asymmetric information; Abnormal returns